A morphometrical study on the skull of Padovana chicken. Issue 3 (3rd July 2018) - Verdiglione, Rina; Rizzi, Chiara
Abstract: A trial was carried out to study the head and skull characteristics in a crested chicken breed with cerebral hernia located in a frontal bony protuberance, an uncrested chicken hybrid strain and their relative crosses. Males and females from five genotypes were used: two Padovana breed varieties (two colour plumages: Padovana argentata, silver -PA- and Padovana camosciata, chamois -PC-), the relative cross (PCxPA), a commercial single comb medium-growing strain (Berlanda gaina [B]) and the cross between PC and B (PCxB). As regards skull dimensions B showed heavier, longer, and wider skull than Padovana group ( p < .001); the cross PCxB had skulls heavier than Padovana purebreds ( p < .05). In the Padovana purebreds the frontal bone height varied from 9.2 to 16.2 mm, whereas in the groups with B component the height ranged from 4.2 to 6.8 mm. The frontal bone height was higher in PC and PCxPA than in PA ( p < .01), whereas B and PCxB did not show any bony protuberance. No correlation resulted in Padovana groups between the frontal bone height and the skull length and width. A positive relationship between frontal bone height and skull height was significant only in PCxPA. For the skull characters of PCxPA both the two genotypes seems to be involved and no predominant and relevant effect of only one genotype was seen. The PCxB cross showed relevant differences in the skull morphometry, particularly in the absence of frontal bony protuberance and in the presence of comb.